Research Progress on the Extraction and Identification of Key Components of Grain Odorants and Their Applications in Grain Storage - LI Hui, HONG Xiwen, WANG Zhengyan, WANG Yanyan (Shipin Kexue)
The composition of grain odorants can be influenced by various factors, such as the type of grain, storage conditions, storage duration and pollution of harmful organisms. The type and content of odor substances can timely reflect whether grains are spoiled or damaged by harmful organisms. In this paper, we summarize the techniques used for the extraction and identification of grain odorants and the composition of odorants in grains in different states, revealing that alkanes, acids, aldehydes, alcohols and other substances impart a unique odor to grains. However, the composition of grain odorants varies greatly depending on the storage environment and the conditions of grains. Then, we discuss the analytical methods for the determination of the characteristic odor compounds in grains and review the possible metabolic pathways of the key odorants in grains. In addition, we summarize the characteristic odorants in rice and wheat including 2-acetyl-1-pyrroline (2-AP), whose formation mechanism in rice has been tentatively confirmed. Finally, we outline the application of odorants in the field of food security and storage, and we suggest that in-depth analysis and mining of data on grain odorants and development of new predictive models for rapid and accurate detection of grain quality will be an important direction for future research on grain odorants. At the same time, some odorants have been confirmed for their potential in the prevention and control of harmful organisms in granaries and will be an important source of new environmentally friendly grain protectants in the future.